Pengaruh Gaji Dan Work-Life Balance Terhadap Minat Berkarir Mahasiswa Akuntansi Di Big 4 Dengan Social Influence Sebagai Variabel Mediasi - Clarissa Aleta Hartono Junus; Amelia Setiawan; Hamfri Djajadikerta (Sekolah Tinggi Ilmu Ekonomi Cendekia Bojonegoro, 2026)
This study aims to identify the factors that influence accounting students’ career interest in the Big 4, with social influence serving as a mediating variable. This study employs a quantitative approach with an explanatory design to elucidate the causal relationships among the variables under investigation. The sample consists of 111 accounting students from various universities in Indonesia, collected through the distribution of a questionnaire. The analysis technique used is Partial Least Squares Structural Equation Modeling (PLS-SEM) with the assistance of the SmartPLS application. This study adopts the Modified Theory of Planned Behavior (Modified TPB) by replacing the subjective norms component with social influence to make it more relevant. The results indicate that salary was not found to have a direct effect on career interest but does influence social influence. Social influence was found to influence career interest, whereas work-life balance was not found to influence career interest. Additionally, salary was found to influence career interest through social influence as a mediating variable. These findings provide important implications for Big 4 Public Accounting Firms in understanding the factors that can influence the career interest of accounting students.